Quantitative thermal comfort analysis of traditional Perak Malay Houses Aida/ Afifah Mior Shahrin and Mohamad Zaki Yusof - Mior Shahrin, Afifah; Yusof, Mohamad Zaki (2018)
This research is conducted to determine the thermal comfort condition in traditional Malay houses in Perak. There is limited scientific study to prove that the traditional Malay house is comfortable despite the high outside temperatures, since most studies are done qualitatively. The traditional Malay houses are under threat of decay due to lack of maintenance and care. Most of their roofs have been replaced with other materials such as metal which cause uncomfortable internal condition. The measurement of air temperature, relative humidity and air velocity were taken inside two different types of traditional Perak Malay houses: the Kutai and the Perak house. Both of the houses studied are newly built and located in Meru, Ipoh. The measurements taken are compared with the comfort range standards specified by MS1525:2007. Bioclimatic chart shows the results taken fall outside the recommended comfort zone. The data showed that the high temperature inside both houses are found to be above the recommended comfort range. The measurements of air velocity and relative humidity are found to be within the recommended comfort ranges.